Chemical composition and antioxidant potential of essential oil and oleoresins from anise seeds (Pimpinella anisum L.) - Singh, Gurdip (2008)
Recently, interest in plant-derived food additives has grown, mainly because of toxic effects associated with synthetic antioxidants. In the present study, the chemical composition and antioxidant properties of essential oil and oleoresins of the seeds of anise (Pimpinella anisum) was investigated. Trans-anethole (90.1%) was the major component in anise oil while oleic acid was the major compound in all the oleoresins. The antioxidant activities were assessed by inhibition of linoleic acid peroxidation, 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging, Fe3+ reducing power and various lipid peroxidation assays. The anise oil and its methanol oleoresin showed highest antioxidant activity, even higher than BHA and BHT. However, the antioxidant activities of other oleoresins were somewhat lower. The results obtained from various experiments clearly establish the antioxidant potency of anise oil and its methanol and ethanol oleoresins, which can be utilized for protecting fat-containing foods.